Response of Cocoa (Theobroma cacao L.) Seedling Growth on Various Growing Media and Organic Plant Supplements - Arum, Ayu Puspita; Innaya, Lutfika Revi; Setiyono, Setiyono; Rosyady, Muhammad Ghufron (Indonesian Coffee and Cocoa Research Institute, 2023)
Cocoa (Theobroma Cacao L.) as a plantation crop which success is determined by healthy and quality seedlings. The use of planting media with a mixture of manure and plant organic supplements may result in healthy soil because it contains soil microorganisms that are beneficial and may support the growth of cocoa seedlings. Purpose of this study was to determine the initial growth response of cocoa seedlings on various growing media and dosages of an organic plant supplement as liquid organic fertilizer. The research was conducted in February–September 2022 in a nursery located in Kradenan, Purwoharjo, Banyuwangi Regency and in Agricultural Laboratory of University of Jember, Bondowoso Campus, Bondowoso Regency. Study was carried out in a 4 x 4 factorial using a randomized block design with three replications. The first factor was planting media which consisted of four levels of treatment, namely soil + chicken manure, soil + goat manure, soil + cow manure, and soil + rabbit manure. The second factor was dose of organic plant supplement which consisted of 4 levels, namely the control treatment of 0, 50, 100, and 150 mL polybag-1. Data were analyzed using analysis of variance and follow-up tests using Duncan’s multiple range test at 5% level. Variables observed included seedling height, number of leaves, stem diameter, leaf length, leaf width, number of roots, root length, fresh weight, and dry weight of seedlings. The results showed that there was an interaction effect on all parameters except seedling height, number of leaves, and number of roots. The conclusion of the study showed that there was an effect of interaction treatment with the best treatment combination planting media using cow manure and organic plant supplement dose of 50 mL polybag-1.